Concomitant fulvestrant with reirradiation for unresectable locoregional recurrent estrogen receptor positive (ER+) breast cancer: A case report and narrative review. Issue 30 (24th July 2020) - Ding, Jingxian; Guo, Yonghong; Jiang, Xiaoliu; Li, Kai; Fu, Wenbing; Cao, Yali
Abstract: Rationale: Locoregional recurrence of breast cancer is a challenging issue for clinicians. Treatment options for unresectable recurrent estrogen receptor positive (ER+) breast cancer in previously irradiated area are limited. Some studies showed concomitant fulvestrant with radiation therapy might increase radiosensitivity compared with radiation alone in vitro, no in vivo reports yet. Patient concern: Here, we present a case report and make a narrative review of concomitant fulvestrant with radiation therapy for unresectable locoregional recurrent ER+ breast cancer. The patient was treated with modified radical mastectomy in 2015, adjuvant chemotherapy, radiotherapy, followed by exemestane until November 2018, relapsed in internal mammary lymph nodes with sternum involved. Diagnosis: The final diagnosis was breast cancer internal mammary lymph nodes metastasis with sternum involved. Interventions: After diagnosis was made, concurrent fulvestrant with reirradiation as a palliative treatment were proposed under multiple disciplinary team. Outcomes: There was a good clinical response, enabling curative chance with radiation therapy to a total dose of 60 Gy. Computed tomography scan revealed no evidence of residual tumor. Lessons: As far as we know, this is the first report concerning concomitant fulvestrant with reirradiation for unresectable locoregional recurrent ER+ breast cancer. Since no severe adverse events were observed, this strategy could be a suitable "loco-regional rescue therapy" to further reduce tumor progression or even reach a curative effect. Studies of this treatment strategy in randomized clinical trials are warranted to further assess its safety and effectiveness.